Spontaneous resolution of a tumor like pulmonary sarcoidosis - Moatemri, Zied; Soussi, Ghassen; Dabboussi, Salsabil; Mhamdi, Samira; Aichaouia, Chiraz; Khadraoui, Mohsen; Cheikh, Rezaik (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
We report a case of thoracic sarcoidosis in a 72-year-old female, snuff taker, who presented with multinodular pulmonary lesions on chest x-ray. Clinical and biological findings were poor. Thoracic imaging showed soft tissue density nodules with irregular borders. The diagnosis of ‘cannon ball’ metastases was suspected. A thorough investigation strategy could not prove malignancy. A complete radiologic clearing was obtained spontaneously within three months. A rereading of pathology slides performed afterwards showed multinucleated giant cells on hemorrhagic background with a lymphocytic alveolitis. The diagnosis of pseudotumoral sarcoidosis was made. The clinical course was favorable with a 6years follow-up.